Development and Validation of an Analytical Procedure for the Determination of Caffeic Acid in Nonea rossica Herb by HPLC - V. V. Velichko; A. V. Lastovka; M. E. Kartashova; A. A. Gaiduk; D. S. Kruglov (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. According to the literature, alcoholic extracts of Nonea rossica Steven have anticoagulant, antimicrobial, and antifungal properties, which may be due to the presence of caffeic acid and its derivatives in the plant. The standardisation of this herbal drug requires the development of an analytical procedure for the quantitative determination of caffeic acid, and the most promising method for this is high-performance liquid chromatography (HPLC).AIM. This study aimed to develop and validate an analytical procedure for the quantitative determination of caffeic acid in Nonea rossica herb by HPLC.MATERIALS AND METHODS. The study focused on the aerial parts of Nonea rossica plants collected in a steppificated meadow in the Novosibirsk Region during the flowering stage. The study used an Agilent 1100 Series HPLC system equipped with a Zorbax SB-C18 column (150 × 2.1 mm, 3.5 μm) and a detector operating at a wavelength of 330 nm.RESULTS. The authors selected chromatographic conditions to obtain one peak per one molecular form of caffeic acid, an acceptable resolution of the extract components, and the maximum intensity of the analyte peak. The gradient elution conditions developed in this study were as follows: a two-component mobile phase, including a 0.01 M aqueous solution of KH2PO4 with a pH of 2.70 (Solvent A) and methanol (Solvent B), and a flow rate of 0.25 mL/min. Under these conditions, caffeic acid eluted at 13.5 minutes, and the total analysis time was 60 minutes. The analytical procedure was validated for its specificity, analytical range, detection limit, quantitation limit, accuracy, repeatability, and intralaboratory precision.CONCLUSIONS. The developed and validated analytical procedure for the quantitative determination of caffeic acid in Nonea rossica herb by HPLC provides results with a relative standard deviation of ≤5.0%. The analytical procedure can be used to standardise the herbal drug Noneae rossicae herba for further use in medicinal practice.